Effects of a simulated marine heatwave on the structure and composition of Mediterranean plankton in a mesocosm study - Zoé Eglaine; Justine Courboulès; Francesco Cipolletta; Cécile Roques; Tanguy Soulié; Diana Sarno; Behzad Mostajir; Francesca Vidussi (PLoS ONE, 2025)
Coastal marine systems are particularly affected by marine heatwaves (MHW), which affect organisms, including plankton communities, that are essential for ecosystem function and productivity. To study their effects on plankton food web components, an in situ mesocosm experiment was conducted in Thau Lagoon (Mediterranean Sea, South France) from May to June 2019. The two conditions were applied in triplicate. A MHW of + 3 °C above the natural lagoon water temperature was applied to three mesocosms and maintained for the first 10 days of the experiment. Afterward heating was discontinued, and temperatures returned to ambient levels for the remaining 10 days. The other three mesocosms were maintained at natural water temperatures throughout the experiment. Phytoplankton responded positively to MHW, whereas protozooplankton and viruses exhibited significant negative responses. The decrease in protozooplankton, which predominantly preyed on phytoplankton, can be explained by the increase in metazooplankton observed under MHW. Increased predation by metazooplankton on protozooplankton reduced their grazing pressure on phytoplankton, allowing them to proliferate. Simultaneously, metazooplankton directly grazed on larger phytoplankton cells, thereby reinforcing the shift in community composition towards smaller species following the simulated MHW. These combined top-down effects led to pronounced changes in both the structure and size of phytoplankton communities under MHW condition, driven by trophic cascades within the planktonic food web. Plankton functional group stability metrics showed that smaller communities were more resistant to MHW than larger communities. Nanophytoplankton, autotrophic flagellates, heterotrophic dinoflagellates, and tintinnids exhibited minimal recovery, whereas other plankton communities displayed a pronounced capacity for full or near-complete recovery following MHW. The contrasting resistance, resilience, and recovery of planktonic functional groups to MHW led to a restructuring of the planktonic food web and its function, with potential consequences for key ecological processes in the pelagic ecosystem.